Double Fragility: The Care Crisis in the Time of the Pandemic - Alexandra Scheele; Helene Schiffbänker; David Walker; Greta Wienkamp (Gender a Výzkum)
The COVID-19 pandemic exposed and reinforced the structural crisis in paid and unpaid care work. On the one hand, pandemic-related closures of schools and childcare facilities increased the fragility of unpaid care arrangements, which are mainly organised by women. On the other hand, high infection and hospitalisation rates exacerbated the difficult working conditions in health-care professions, ranging from low wages and long working hours to high levels of mental and physical stress. Drawing on interviews conducted in an ongoing project in the German and Austrian health-care sector, this article investigates, from a gender perspective, how employees in health-care professions, who are at the very centre of both the unpaid and paid care crises, experienced this precarious situation during the pandemic. We suggest that the female-dominated sectors of paid and unpaid care work experienced further devaluation during the COVID-19 pandemic, while attempts to valorise their work were rather short-lived. We further argue that the structural crisis in paid care work is threatening the functionality of the health-care sector.